Comparison of the effect of vitamin D supplementation and metformin on symptoms of polycystic ovary syndrome (Research, Society and Development, 2022)
Introduction: Polycystic ovary syndrome (PCOS) is characterized as an endocrine, reproductive and metabolic disease, it is a complex and heterogeneous disorder with a prevalence of 5 to 10% in women of reproductive age. Objective: This study aims to evaluate the effect of vitamin D supplementation compared to the use of the drug metformin on the symptoms of Polycystic Ovary Syndrome. Methodology: This research is characterized as descriptive. Results and Discussion: Metformin is a medication widely used in the treatment of PCOS symptoms. Vitamin D, on the other hand, is a pro-hormone well known for its calcium and phosphorus homeostasis function. Conclusion: There was a benefit in both approaches, however, there are differences in terms of side effects and the number of studies to prove efficacy.